Orthopantomography as One of the Additional Diagnostic Methods in Dental Implantology: Current State of Prevalence of the Issue Among Different Age Groups of the Population: Part 1 - Skibitskyi Вадим; Bohatyreva Дарина (Actual Dentistry, 2026)
Abstract. Prosthetic rehabilitation using dental implants occupies a leading position among methods for restoring dentition defects. It ensures high functional efficiency and long-term aesthetic outcomes. Recently, there has been a steady increase in the number of implant procedures of varying complexity among patients of different age groups requiring prosthetic treatment. The success of implant therapy depends on a number of criteria, including the assessment of the patient’s somatic status, proper treatment planning, and radiological diagnostics. Orthopantomography is a primary diagnostic method; however, for successful implant planning, its combination with cone-beam computed tomography is advisable. Such a comprehensive approach enhances planning accuracy, minimizes the risk of complications, and improves the long-term outcomes of implant treatment.